2013
DOI: 10.15376/biores.8.3.4756-4765
|View full text |Cite
|
Sign up to set email alerts
|

Selected Properties of Heat-Treated Eastern Red Cedar (Juniperus virginiana L.) Wood

Abstract: The objective of this study was to evaluate the effect of heat treatment on properties including oven-dry density, weight loss, surface roughness, shear strength, and hardness of eastern red cedar (Juniperus virginiana L.). The anatomical structures of samples were also examined by scanning electron microscope (SEM). Two different heat treatment schedules, with temperatures of 130°C and 160°C and 3 and 7 h exposure times, were considered for the experiment. A stylus method was employed to evaluate the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, it is well known that overly high temperatures may reduce the mechanical strength of wood based on the finding in previous studies (Korkut et al 2008(Korkut et al , 2013Kesik et al 2014;Pavel et al 2014). For example, Pavel et al (2014) determined a significant decrease of 47% in value of shear strength for thermally treated wood with natural wood when compared with natural oak -oak bonding.…”
Section: Introductionmentioning
confidence: 90%
“…However, it is well known that overly high temperatures may reduce the mechanical strength of wood based on the finding in previous studies (Korkut et al 2008(Korkut et al , 2013Kesik et al 2014;Pavel et al 2014). For example, Pavel et al (2014) determined a significant decrease of 47% in value of shear strength for thermally treated wood with natural wood when compared with natural oak -oak bonding.…”
Section: Introductionmentioning
confidence: 90%
“…There are different processes by which the hygroscopicity of wood can be reduced and many studies have been carried out in the literature on different processes [5,6].Heat treatment is the oldest and simplest method by which wood hygroscopicity can be effectively decreased. In addition, the dimensional stability, biological resistance and durability of the wood can also be improved [7][8][9]. It was showed that the heat treatment of wood not only reduced the hygroscopicity but also caused physical changes in the wood such as surface modification, which can significantly affect the adhesive bond…”
mentioning
confidence: 99%